2011
DOI: 10.1128/jvi.01924-10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Valency of a Glycoprotein B-Specific Monoclonal Antibody on Neutralization of Herpes Simplex Virus

Abstract: Herpes simplex virus (HSV) glycoprotein B (gB) is an integral part of the multicomponent fusion system required for virus entry and cell-cell fusion. Here we investigated the mechanism of viral neutralization by the monoclonal antibody (MAb) 2c, which specifically recognizes the gB of HSV type 1 (HSV-1) and HSV-2. Binding of MAb 2c to a type-common discontinuous epitope of gB resulted in highly efficient neutralization of HSV at the postbinding/prefusion stage and completely abrogated the viral cell-to-cell sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 68 publications
4
85
0
Order By: Relevance
“…Because epitope alterations in HSV-2 vs. HSV-1 isolates could be excluded by epitope sequencing, we concluded that the different neutralization efficacy of mAb hu2c toward HSV-1 vs. HSV-2 isolates is the consequence of higher HSV-2 genome copy numbers, resulting in an increase of noninfectious virus particles, as we have reported earlier (20).…”
Section: Prophylactic and Therapeutic Treatment With Mab Hu2c Protectssupporting
confidence: 57%
See 4 more Smart Citations
“…Because epitope alterations in HSV-2 vs. HSV-1 isolates could be excluded by epitope sequencing, we concluded that the different neutralization efficacy of mAb hu2c toward HSV-1 vs. HSV-2 isolates is the consequence of higher HSV-2 genome copy numbers, resulting in an increase of noninfectious virus particles, as we have reported earlier (20).…”
Section: Prophylactic and Therapeutic Treatment With Mab Hu2c Protectssupporting
confidence: 57%
“…Hence, CDR coding gene segments of the murine donor-antibody 2c (i.e., 2c V L -CDR1/2/3 and 2c V H -CDR1/2/3) were grafted into acceptor frameworks coding for IGHV2-70 and IGKV2-40, respectively. Humanized or murine variable domain encoding genes (20) were subsequently cloned into Ig expression vectors containing a human constant heavy γ1 chain, and a human constant κ chain, respectively. After stable cotransfection of vectors into Sp2/0-Ag14 cells, humanized IgG hu2c and chimeric IgG ch2c were produced and purified from cell culture supernatants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations